Health system characteristics and evidence-based asthma care - Crawford, Alice L.; Jones, Gareth H.; Scullion, Jane; Ryan, Dermot; Blakey, John D. (Frontiers in Allergy, 2025)
Asthma is a common and complex syndrome, and a major cause of morbidity and healthcare costs. Clinicians have an array of evidence-based investigations and effective interventions at their disposal, but outcomes have not improved as much as trial evidence would suggest they could. This article discusses drivers behind this discrepancy using illustrative examples to highlight information gaps and barriers that impair the delivery of community and emergency asthma care and appropriate referral to specialist asthma services. It highlights organizational issues in the current system that lead to disjointed care that varies in quality. It also explores problems such as the adequacy of training for healthcare professionals, divergence from best practice guidance, and an acceptance amongst patients and practitioners of poor asthma control. This, along with inherent problems in the diagnosis of this heterogeneous disease, facilitates and perpetuates suboptimal care and outcomes. To help address the outcome gap, we discuss the potential for relatively simple, achievable and cost-effective actions that could potentially be taken by clinicians together with commissioners and managers of healthcare systems.